Simulation for a floating roof behavior of cylindrical storage tank due to wind load (Wind velocity effect on sloshing) - Shoichi YOSHIDA; Shinichi KURODA; Hidesaku UEJIMA; Kazuo ISHIDA; Masaki SHIRATORI; Kazuyoshi SEKINE; Tomohiko TSUCHIDA (Nihon Kikai Gakkai ronbunshu, 2014)
Floating roofs are used on large cylindrical storage tanks to prevent evaporation of oil. The single-deck floating roof considered herein consists of a thin circular plate, referred to as a "deck", attached to a buoyant ring with a hollow rectangular cross section referred to as a "pontoon". The deck plate is deformed to be created waves and is subjected to cyclic bending due to the wind load. Since this leads to the initiation of fatigue cracks at the welded joints, it is important to understand the wave characteristics in the deck plate. The authors have previously reported a computational fluid dynamics (CFD) analysis of a cylindrical storage tank under a wind load. The present paper describes an axisymmetric finite element analysis of the sloshing response of a single-deck floating roof on a cylindrical storage tank using the previous CFD results as the load conditions. It is assumed that the liquid is incompressible and inviscid, the roof exhibits linear elastic behavior, and the sidewalls and bottom of the tank are rigid. The effect of the wind velocity on the frequency and amplitude of vibrations in the deck plate is investigated. As a result, the relation between the amplitude of vibration and the wind velocity is shown. The predominant period of bending stress vibration of the deck plate is shorter than that of the waves.